THE IMPACTS OF THE COVID-19 PANDEMIC ON THE INVENTORY MANAGEMENT DECISIONS OF THE E-COMMERCE ENTREPRENEURS IN NAKHON RATCHASIMA, THAILAND - PEARMUNWAI, Sasiwimon; SIRINON, Warayu; Susena, Wuttiya Akarawichayanon (Asian Administration and Management Review, 2022)
This research aims to study the impact levels of the COVID-19 pandemic and the relationship of such impact on the inventory management decisions. collecting information from e-commerce entrepreneurs in Nakhon Ratchasima, Thailand. The questionnaires were distributed and collected the final good samples from 370 persons. The data was statistical analysed with frequency distribution, percentage, mean, standard deviation and multiple regression. The results found that the coronavirus pandemic had the impact on inventory management decisions of the e-commerce entrepreneurs in Nakhon Ratchasima, Thailand at a high levels. There were the impacts in terms of declining in demand for products and services and the sudden changes in government policy influenced economic order quantity management decisions. The management of the working environment influenced reorder point level and lead time management decisions at the significance level of 0.01